The Impact of Multi-Dimensional Incentives on the Performance of Rail Transit PPP Projects - Zheng Zhu; Yining Yuan; Lei Zhang; Jianfeng Zhao; Jingfeng Yuan (Buildings)
This study investigates how different types of incentives impact the performance of rail transit PPPs, focusing on their construction and operational phases. By surveying 121 practitioners working in the Chinese rail transit industry, we propose a new classification of incentives (i.e., control-oriented, neutrality-oriented, and recognition-oriented incentives) based on psychological theories to broaden the categorization of “positive” (rewards) and “negative” (punishment) incentives. We further explore how these multi-dimensional incentives influence project performance by surveying another 256 industry professionals. Our findings reveal that (1) in addition to punishments, performance-based payment/bonus, credit ratings, and reputation mechanisms are newly recognized as control-oriented incentives, which can restrain the autonomy of the private sector; (2) control-oriented incentives positively influence project performance in the construction phase where clear, measurable goals are available, but their impact diminishes in the operational phase; (3) recognition-oriented incentives enhance project performance in both construction and operational phases (especially the latter), fostering long-term sustainability; and (4) neutrality-oriented incentives focus on risk allocation and collaboration between public and private sectors, showing a modestly positive effect in the operational phase. As such, the study provides decision-makers in the rail transit industry with valuable insights to enhance project performance effectively when implementing incentive policies.